DEVELOPING RULIBA MEDIA BASED ON LOCAL WISDOM FOR LEARNING THE BALANCE OF ECOSYSTEM IN THE NATURAL SCIENCE SUBJECT - Rizki Sisfadilla; Nana Hendracipta; Encep Andriana (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to develop ruliba media based on local wisdom for learning the balance of ecosystem in the natural science subject at grade V SD a well as to determine the feasibilityof the learning media and the users’ response after using ruliba media based on local wisdom. This study used research and development as the research method, with Borg and Gall development model that have been modified by Sugiyono into 6 stages, namely: 1) problem analysis,2) data collection, 3) product design, 4) design validation, 5) design revision and 6) product testing (limited trial). The product of this research was ruliba learning media based on local wisdom for learning the balance of ecosystem in the natural science subject at grade V SD. The feasibility level of ruliba media was determined based on the assessment results from the experts consisting of material experts, media experts, ethnopedagogic experts, as well as teachers’ and students’ response. The average percentage of each assessment result was respectively 97.5%, 92.5%, 81%, 100%, and 95.6% which achieved the category of “very feasible” and “very good”. Based on this result, it could be concluded that local wisdom- based ruliba learning media was suitable to be used as a learning media for ecosystem balance lesson.